1987
DOI: 10.1172/jci113232
|View full text |Cite
|
Sign up to set email alerts
|

Soybean protein diet increases low density lipoprotein receptor activity in mononuclear cells from hypercholesterolemic patients.

Abstract: The effect of two diets containing different protein sources (animal vs. soybean) on the low density lipoprotein (LDL) receptor activity was tested in freshly isolated mononuclear cells from 12 individuals with severe type II hyperlipoproteinemia. The two diets, both taken for 4 wk in a crossover design were of otherwise identical composition. During the soybean protein diet period, total cholesterol was reduced by 15.9% and LDLcholesterol by 16.4%. The diet containing animal proteins exerted no significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(100 citation statements)
references
References 33 publications
3
90
1
4
Order By: Relevance
“…Indeed, the controversy over the need to have isoflavones retained within soy protein is not resolved. However, there is a suggestion that isoflavones, like oestrogens, may upregulate the LDL receptors (Lovati et al, 1987;Baum et al, 1998) and thereby accelerate clearance of LDL-C from the circulation. If that requires interaction with oestrogen receptors in liver and other tissues, then biochanin/genistein might be expected to exert a greater effect than formononetin/ daidzein.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the controversy over the need to have isoflavones retained within soy protein is not resolved. However, there is a suggestion that isoflavones, like oestrogens, may upregulate the LDL receptors (Lovati et al, 1987;Baum et al, 1998) and thereby accelerate clearance of LDL-C from the circulation. If that requires interaction with oestrogen receptors in liver and other tissues, then biochanin/genistein might be expected to exert a greater effect than formononetin/ daidzein.…”
Section: Discussionmentioning
confidence: 99%
“…The lower sulfur amino acid content of soy protein may help to reduce calcium excretion in comparison to consuming animal proteins, so it lowers the risk of osteoporosis. Intake of soy protein can decrease cholesterol level of serum, so the soy protein can help to reduce the risk of kidney disease and heart disease in high risk individuals 15 . The contents of vitamin B 12 , which is essential for the nervous system, in Chou sufu (strong smell sufu) and red sufu produced in Beijing were determined.…”
Section: Research On Traditional Fermented Soybean Foods In Chinamentioning
confidence: 99%
“…Genistein has been also shown to decrease cholesterol synthesis in cultured HepG2 [7] and inhibits HMG-CoA reductase activity in MCF-7 human breast cancer cells [17]. It has been suggested that the soy proteins enhance the expression of the LDL receptor in cultured human hepatoma cells [26], animals, and hypercholesterolemic Type 2 diabetic patients [24,25]. A similar effect has been observed with a soy protein polypeptide in cultured HepG2 cells [27].…”
Section: Introductionmentioning
confidence: 84%